Combination of a sorting grid and a square mesh panel to optimize size selection in the North-East Arctic cod (Gadus morhua) and redfish (Sebastes spp.) trawl fisheries - Sistiaga, Manu Berrondo; Herrmann, Bent; Grimaldo, Eduardo; Larsen, Roger B.; Olsen, Leonore; Brinkhof, Jesse; Tatone, Ivan (ICES Journal of Marine Science, 2017)
This is a pre-copyedited, author-produced version of an article accepted for publication in ICES Journal of Marine Science following peer review. The version of record Sistiaga, M.B., Herrmann, B., Grimaldo, E., Larsen, R.B., Olsen, L., Brinkhof, J. & Tatone, I. (2017). Combination of a sorting grid and a square mesh panel to optimize size selection in the North-East Arctic cod (Gadus morhua) and redfish (Sebastes spp.) trawl fisheries. ICES Journal of Marine Science. 75(3), 1105-1116 is available online at: https://doi.org/10.1093/icesjms/fsx231 Sorting grids and square mesh panels are the two most-applied technical devices to supplement codend size- and species-selection in demer- sal trawls. In the Barents Sea gadoid fishery, the compulsory size-selectivity system comprises a mesh section with a sorting grid followed by a diamond mesh codend. We tested the size-selective performance of a new sorting section that comprised a sorting grid combined with a square mesh panel as a potential alternative for the grid sections currently in use. The new sorting section was shorter and therefore more maneuverable than the existing sorting grid sections. The investigation was carried out on cod and the bycatch species redfish. The grid was found to contribute to the largest proportion of fish release, and the release through the square mesh panel was low. But, the results showed that the grid was successful at guiding fish not escaping through the grid to a second selection process in the panel. However, the square mesh panel did not result on the intended release efficiency except for the smallest sizes of fish, most likely because the guiding angle of the grid and the square meshes in the panel used did not provide a suitable escape path for the desired size range of fish. Therefore, optimizing the mesh size/shape in the panel and/or the guiding angle for the grid potentially could lead to the desired selectivity pattern in the new sort- ing section.